The Role of Governance and Transparency in Combating Corruption - Al-Shalfan , Adel (The Arab Journal of Administration, 2021)
The study aimed to address the role of governance and transparency in combating corruption, and to identify the mechanisms and strategies necessary to combat corruption. The descriptive approach adopted. It is theoretical study that relied on reviewing the literature of governance, transparency and corruption. The study reached several results, the most important of which is that governance helps achieve ensuring integrity and transparency for organizations, and governance is of great importance in combating corruption, because it provides organizations with an organizational structure that enables them to achieve their goals in the best possible way. Governance also works to spread transparency in all the organization’s actions in a way the contributes to creating a relationship that is characterized by clarity and transparency in all transactions, and transparency is considered a safer work environment, and encourages better utilization of the organization, where performance is better and more transparent. In light of these results, a number of recommendations have been developed that may contribute to activating the role of governance and transparency in combating corruption, the most important of which are: establishing strict laws to prevent corruption in order to have effective systems to evaluate the performance of organizations through the principle of accountability for all the cost of corruption so that its not to be justified for freezing canceling anti-corruption plans due to their high cost over corruption, and spreading public awareness, in order to raise the level of civilized society and consider fighting administrative corruption in which everyone must participate.